2007
DOI: 10.1179/joc.2007.19.5.495
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility and β-Lactamase Production of Anaerobic and Aerobic Bacteria Isolated from Pus Specimens from Orofacial Infections

Abstract: Most suppurative orofacial infections are polymicrobial. Information regarding the antimicrobial susceptibility of the microorganisms involved can be useful in the choice of an effective antibiotic therapy. In this study we determined the antimicrobial susceptibility of a total 235 anaerobic and aerobic bacteria recently isolated from pus specimens of orofacial infections. All the viridans streptococci were susceptible to penicillin, cefotaxime, cefoxitin, imipenem and levofloxacin. Imipenem and levofloxacin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…The results of the present study showed that three antibiotics including amoxicillin/clavulanic acid, doxycycline and azithromycin had 100% activities against P. gingivalis which can provide alternative antibiotics to treat the patients whenever indicated. The fact that 12 % of the bacteria were resistant or intermediate resistant to amoxicillin but 100 % were sensitive to amoxicillin/clavulanic acid, indicates that resistance of P. gingivalis to β-lactam antibiotics are due to β-lactamase production (25,26). Low values of MIC 50 and MIC 90 of the three effective antibiotics were also noticed in this study, which could suggest that systemic antibiotic therapy may deliver adequate drug inside the infected teeth (27,28).…”
Section: Discussionsupporting
confidence: 50%
“…The results of the present study showed that three antibiotics including amoxicillin/clavulanic acid, doxycycline and azithromycin had 100% activities against P. gingivalis which can provide alternative antibiotics to treat the patients whenever indicated. The fact that 12 % of the bacteria were resistant or intermediate resistant to amoxicillin but 100 % were sensitive to amoxicillin/clavulanic acid, indicates that resistance of P. gingivalis to β-lactam antibiotics are due to β-lactamase production (25,26). Low values of MIC 50 and MIC 90 of the three effective antibiotics were also noticed in this study, which could suggest that systemic antibiotic therapy may deliver adequate drug inside the infected teeth (27,28).…”
Section: Discussionsupporting
confidence: 50%
“…Since the use of antibiotics is restricted to severe and complicated abscess infections, it seems prudent to use amoxicillin, a semisynthetic penicillin with a broader spectrum of antimicrobial activity than penicillin V. In addition, amoxicillin may provide more rapid improvement in pain or swelling, and patient compliance with the prescribed regimen may be better because of the longer dosage interval of amoxicillin (209). In even more serious cases, including life-threatening conditions, association of amoxicillin with either clavulanic acid or metronidazole may be required to achieve optimum antimicrobial effects as a result of the spectrum of action being extended to include penicillin-resistant strains (208,210). A randomized clinical trial (199) compared the efficacy of adjunct therapy with amoxicillin-clavulanic acid to that with penicillin V in the treatment of acute apical abscess following surgical drainage and either tooth extraction or root canal intervention and reported that, even though symptoms improved in all patients, those receiving amoxicillin-clavulanic acid recorded a significantly greater decrease in symptoms during the second and third days.…”
Section: Treatment Of the Acute Apical Abscessmentioning
confidence: 99%
“…All samples were inoculated on Columbia agar with 5 % sheep blood (BD Becton Dickinson), Haemophilus Test Medium (HTM) agar (BD Becton Dickinson) and Brucella blood agar with haemin and vitamin K 1 (BD Becton Dickinson). Columbia blood and HTM agar plates were incubated under aerobic conditions and in an atmosphere of 10 % CO 2 at 35 uC for 24-48 h. Supplemented Brucella agar plates were incubated anaerobically in GasPak 100 Jars (BD Becton Dickinson) at 35 uC for 72 h; the incubation was continued for at least 7 days, even in the absence of bacterial growth (Blandino et al, 2007). From each bacterial plate, representative colonies of each morphological type were subcultured on selective media (Murray et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…From each bacterial plate, representative colonies of each morphological type were subcultured on selective media (Murray et al, 2007). Identification of bacteria was made by colony and cellular morphology, staining characteristics and commercially available microbiological identification systems, such as API 20 Strep, API 20 E, API 20 NE, API NH, API 20 A, Rapid ID 32 A and API ZYM (bioMérieux) (Summanen et al, 1993;Blandino et al, 2007;Murray et al, 2007).…”
Section: Methodsmentioning
confidence: 99%